In Vitro Antimicrobial Activity of Zodia (Evodia suaveolens) Leaf Extract on Pathogenic Agents Dragon Fruit Plant - Trio Ageng Prayitno; Nuril Hidayati (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2020)
The use of antimicrobials from plant extracts has not been used optimally to control pathogenic agents in dragon fruit plants. The purpose of this research was to determine the antimicrobial activity of zodia (Evodia suaveolens) leaf extracts on pathogenic agents of dragon fruit plants in vitro. The research method is laboratory research with Completely Randomized Design (CRD). The antimicrobial concentrations of zodia (E. suaveolens) leaf extract used six types including 50%, 60%, 70%, 80%, 90%, and 100% with four replications. The research sample was the leaf of zodia (E. suaveolens), Pseudomonas aeruginosa and Fusarium oxysporum strain Malang. Test the antimicrobial activity of zodia (E. suaveolens) leaf extracts on the growth of P. aeruginosa and F. oxysporum using the disc-diffusion method and wells method. The research instrument was used the observation sheet of the diameter of inhibition zone indicated by the clear zone. The diameter of inhibition zone data were analyzed using the One Way ANOVA test. The results showed that the antimicrobial activity of zodia (E. suaveolens) leaf extract significantly inhibited the growth of P. aeruginosa and F. oxysporum (P <0.05). These results recommend zodia (E. suaveolens) leaf extract as an antimicrobial agent for dragon fruit plant pathogens.